Design of a universal low-temperature rotary apparatus for making meat and vegetable products considering the integrated adaptive mechanism - Zahorulko, Andrii; Загорулько, Андрій; Penkina, Nataliia; Пенкіна, Наталія; Zhelieva, Tetiana; Желєва, Тетяна; Chmil, Hanna; Чміль, Ганна; Prykhodko, Maksym; Приходько, Максим; Oleksandr, Kobets; Кобець, Олександр Миколайович; et al. (TECHNOLOGY CENTER PC® Український державний університет залізничного транспорту, 2024)
The object of this study is the implementation of low-temperature processes for the production of meat and vegetable products under the conditions of adding a dried semi-finished product of a high degree of readiness to the recipe when using the designed universal rotary device of continuous action. The rotary device of continuous action for low-temperature processing of meat and vegetable products with a cylindrical working chamber is heated by a film-like resistive electronic heater of the radiating type. It has a stationary wall (with a technical door for unloading and loading the device) and a technical wall (with an opening angle of 90°). On the inner surfaces of the walls, inclined converging ribs with an angle of 25° are installed, which are covered with an electric heater. Semi-finished meat and vegetable products are loaded onto carts with technological containers and mounted on a frameless drum (rotation frequency 0.03...0.06 s–1). The device converts secondary thermal energy into low-voltage power supply voltage (~3...8 W) for autonomous operation of fans. The proposed integrated adaptive mechanism for the system of complex interaction of the agricultural, processing, and production sectors implies the formation of resource efficiency of production processes from "farm to table". The designed device implements the process of frying meat-vegetable bread under conditions of reaching 80 °C in the center of the product. The obtained temperature field data confirm the uniformity of the temperature field during frying of the product (cooking readiness of the product at the initial weight of 650±20 g – 4.0 hours). The introduction of a multicomponent dried fraction based on potatoes, Jerusalem artichokes, zucchini, and carrots into the recipe of meat-vegetable bread reduces the weight loss of the semi-finished product during frying by 12.3 %. It increases the content of calcium, phosphorus, vitamin C accompanied with a decrease in energy value by 28.1 % Об’єктом дослідження є реалізація низькотемпературних процесів виробництва м’ясо-рослинної продукції за умов додавання в рецептуру в’яленого напівфабрикату високого ступеня готовності при використанні розробленого універсального роторного пристрою безперервної дії. дію. Роторний апарат безперервної дії для низькотемпературної обробки м'ясо-овочевих продуктів з циліндричною робочою камерою обігрівається плівковим резистивним електронним нагрівачем радіаційного типу. Має стаціонарну стінку (з технічними дверима для вивантаження і завантаження апарату) і технічну стінку (з кутом розкриття 90°). На внутрішніх поверхнях стінок встановлюють похилі збіжні ребра під кутом 25°, які покривають електронагрівачем. М'ясо-овочеві напівфабрикати завантажують на візки з технологічною тарою і встановлюють на безкаркасний барабан (частота обертання 0,03...0,06 с –1 ). Пристрій перетворює вторинну теплову енергію в напругу живлення низької напруги (~3...8 Вт) для автономної роботи вентиляторів. Запропонований інтегрований адаптивний механізм системи комплексної взаємодії аграрного, переробного та виробничого секторів передбачає формування ресурсної ефективності виробничих процесів від «ферми до столу». Розроблений пристрій реалізує процес смаження м'ясо-овочевого хліба в умовах досягнення 80 °С в центрі продукту. Отримані дані температурного поля підтверджують рівномірність температурного поля під час смаження продукту (кулінарна готовність продукту при початковій масі 650±20 г – 4,0 години). Введення в рецептуру м’ясо-рослинного хліба багатокомпонентної підсушеної фракції на основі картоплі, топінамбура, кабачків, моркви зменшує втрати маси напівфабрикату при смаженні на 12,3 %. Підвищує вміст кальцію, фосфору, вітаміну С при зниженні енергетичної цінності на 28,1 %.
Універсальна конструкція низькотемпературного роторного апарату для приготування м'ясо-овочевих продуктів з урахуванням вбудованого адаптивного механізму
Keywords: meat-vegetable products; м'ясо-овочева продукція; multicomponent vegetable dried semi-finished product; багатокомпонентний овочевий сушений напівфабрикат; frameless technology; безкаркасна технологія; temperature field uniformity; рівномірність температурного поля